2022
DOI: 10.3390/plants11141894
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Oxide Nanoparticles (Fe3O4) on Growth, Photosynthesis, Antioxidant Activity and Distribution of Mineral Elements in Wheat (Triticum aestivum) Plants

Abstract: Engineered nanoparticles (NPs) are considered potential agents for agriculture as fertilizers and growth enhancers. However, their action spectrum differs strongly, depending on the type of NP, its concentrations, and plant species per se, ranging from growth stimulation to toxicity. This work aimed to investigate effects of iron oxide (Fe3O4) NPs on growth, photosynthesis, respiration, antioxidant activity, and leaf mineral content of wheat plants. Wheat seeds were treated with NP for 3 h and plants were grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(37 citation statements)
references
References 51 publications
2
35
0
Order By: Relevance
“…The enhanced soybean growth by Fe-based NMs as compared to unexposed control and EDTA control might be due to the slow and sustained release of bioavailable Fe from NMs that can improve the nutrient efficiency and reduce nutrient surplus during the full life circle. 22,23 The time-dependent dissolution of 10 mg L −1 Fe−P and Fe 3 O 4 NMs in deionized (DI) water indicated that about 0.3% and 0.1% Fe were released from Fe− P and Fe 3 O 4 NMs after 144 h, respectively (Figure S2). These released Fe could easily enter leaves and take part in photosynthesis, nitrogen assimilation, hormone biosynthesis (gibberellic acid, jasmonic acid, ethylene), and flavonoid synthesis to facilitate plant growth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced soybean growth by Fe-based NMs as compared to unexposed control and EDTA control might be due to the slow and sustained release of bioavailable Fe from NMs that can improve the nutrient efficiency and reduce nutrient surplus during the full life circle. 22,23 The time-dependent dissolution of 10 mg L −1 Fe−P and Fe 3 O 4 NMs in deionized (DI) water indicated that about 0.3% and 0.1% Fe were released from Fe− P and Fe 3 O 4 NMs after 144 h, respectively (Figure S2). These released Fe could easily enter leaves and take part in photosynthesis, nitrogen assimilation, hormone biosynthesis (gibberellic acid, jasmonic acid, ethylene), and flavonoid synthesis to facilitate plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Foliar treatment with 5 mg L –1 Fe–P and Fe 3 O 4 NMs, 10 mg L –1 Fe–P, and Fe 3 O 4 NMs, and EDTA-High were most effective for the promotion of fresh weight (Figure S1c,d). The enhanced soybean growth by Fe-based NMs as compared to unexposed control and EDTA control might be due to the slow and sustained release of bioavailable Fe from NMs that can improve the nutrient efficiency and reduce nutrient surplus during the full life circle. , The time-dependent dissolution of 10 mg L –1 Fe–P and Fe 3 O 4 NMs in deionized (DI) water indicated that about 0.3% and 0.1% Fe were released from Fe–P and Fe 3 O 4 NMs after 144 h, respectively (Figure S2). These released Fe could easily enter leaves and take part in photosynthesis, nitrogen assimilation, hormone biosynthesis (gibberellic acid, jasmonic acid, ethylene), and flavonoid synthesis to facilitate plant growth. , Interestingly, the number of nodules significantly improved by 50.0% and 35.4% in the presence of 10 mg L –1 Fe–P and Fe 3 O 4 NMs (Figure e), while all other treatments had no significant differences with control.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, pH and Fe 2 O 3 negatively and significantly associated with Fusarium indicated that can inhibit pathogen. Notably, the content of Fe 2 O 3 increased after plant or plant combined with urban sludge treatments and then enhance plant biomass ( Feng Y. et al, 2022 ). This may be related to that the increase of pH is conducive to the dissociation of iron oxides ( Penn and Camberato, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…There is an urgent need to find affordable and environmentally friendly ways to use NPs as fertilizer to treat plants' iron deficiency-induced chlorosis. [28][29][30] Previous research has demonstrated that low concentrations of Fe 2 O 3 NPs can enhance the SPAD value, soluble sugar content, and soluble protein content in legumes, [31][32][33][34][35][36] watermelon, as well as the growth and germination of Lactuca sativa, 37 soybean, 38 and peanut plants. Fe 2 O 3 NPs cause oxidative stress in plants such as watermelon, citrus, 39 rice, 40 peanut, and soybean 38 when present in high quantities.…”
Section: Introductionmentioning
confidence: 99%